After the Break: Serial Narratives and Fannish Reading. - Moore, Anne. (2017)
Abstract: Borrowing freely from reception studies, psychoanalysis, narrative theory, and queer theory, After the Break presents a model of the engaged serial reader as a fan: one who reads with intense affective investment in both the figure of the author and the narrative world, and does so as part of a community of readers. Each chapter features a Victorian novel and a postmodern serial television show. Juxtaposing these narratives illuminates how their simultaneous status as a series of parts and a coherent whole elicits a set of excessive, "fannish" responses that are shaped by this simultaneity: affection and resentment, desire and satiation, ending and always beginning again. Devoted readers find ways to remain critically engaged with the narratives they love even as they're inescapably reminded of the myriad ways that these texts will inevitably fail them. Since the formal and affective excess of the serial is central to my argument as a whole, I begin with an analysis of the connection between the serial's formal excess and the imaginary relationship between the reader and writer that is established over the serial's run. I then shift my attention to the narratalogical issue of textual boundaries, showing how the disrupted and disruptive limits of the serial are impossible to fix, and how this quality lends the serial its uncanny power over readers. In my third chapter, I examine this power more closely, especially focusing on the ways that serials elicit compulsive reading. I end with a coda that considers Twin Peaks as an example of the serial's inevitable failures, and how this "failure" is key to the form's ability to worm its way into reader's heads.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of English.; Advisors: Joseph Litvak, and Sonia Hofkosh.; Committee: John Lurz, and Robyn Warhol.; Keywords: Literature, and Multimedia.